Evaluating the Effects of the Autonomic Nervous System and Sympathetic Activity on Emotional States - AKBULUT, FATMA PATLAR (Doç. Dr. Necip Şimşek, 2022)
Emotion recognition has attracted more interest by being applied in many application areas from different domains such as medical diagnosis, e-commerce, and robotics. This research quantifies the stimulated short-term effect of emotions on the autonomic nervous system and sympathetic activity. The primary purpose of this study is to investigate the responses of 21 adults by attaching a wearable system to measure physiological data such as an electrocardiogram and electrodermal activity in a controlled environment. Cardiovascular effects were evaluated with heart rate variability indices that included HR, HRV triangular-index, rMSSD (ms), pNN5O (%); frequency analysis of the very low frequency (VLF: 0-0,04 Hz), low frequency (LF: 0,04-0,15 Hz), and high frequency (HF: 0,15-0,4 Hz) components; nonlinear analysis. The sympathetic activity was evaluated with time-varying and time-invariant spectral analysis results of the EDA. The participants who experience calmness had a 4,8% lower heart rate (75,06±16,76 and 78,72±16,52) observed compared to happiness. Negative valance with high-arousal emotions like anger was invariably responded to with a peak in skin conductance level. Besides, negative valance with low-arousal emotions like sadness was allied with a drop in conductance level. Anger, in addition to being the most well-known emotion, elicited coherent time-varying spectral responses.

Duygu tanıma, tıbbi teşhis, e-ticaret, robotik gibi farklı alanlarda birçok uygulama şekli ile gerçeklenerek yüksek ilgi görmüştür. Bu araştırma, duyguların otonom sinir sistemi ve sempatik aktivite üzerindeki uyarılmış kısa vadeli etkisini ölçmektedir. Çalışmanın birincil amacı, kontrollü bir ortamda elektrokardiyogram ve elektrodermal aktivite vb. fizyolojik verileri ölçmek için giyilebilir bir sistem kullanan 21 yetişkin katılımcının tepkilerini araştırmaktır. Kardiyovasküler etkiler, HR, HRV üçgen-indeksi, rMSSD (ms), pNN5O (%); çok düşük frekans (VLF: 0-0,04 Hz), düşük frekans (LF: 0,04-0,15 Hz) ve yüksek frekans (HF: 0,15-0,4 Hz) bileşenlerinin frekans analizi; SD1, SD2 ve SD oranının doğrusal olmayan analizi, sempatik aktivite, EDA'nın zamanla değişen ve zamanla değişmeyen spektral analiz sonuçları ile değerlendirildi. Sakinlik hisseden katılımcıların mutluluğa kıyasla %4,8% daha düşük kalp atış hızına (75,06±16,76 ve 78,72±16,52) sahip olduğu gözlemlendi. Öfke gibi yüksek uyarılma seviyesi sahip olumsuz duygularda her zaman cilt iletkenlik değerleri zirve ölçümleri tespit ettik. Ayrıca, üzüntü gibi düşük uyarılma düzeyindeki negatif duygulara sahip olanlar iletkenlik seviyesindeki bir azalma ile bağlantılıydı. Öfke, en iyi tespit edilebilen duygu olmasının yanı sıra, zamanla değişen tutarlı spektral tepkiler ortaya çıkardığı görüldü.
Otonom Sinir Sistemi ve Sempatik Aktivitenin Duygu Durumu Üzerindeki Etkilerinin Değerlendirilmesi
Keywords: Emotion Recognition; Biomedical Signal Processing; HRV Analysis; Spectral Analysis